Patent ductus arteriosus (also non-hemodynamically significant) correlates with poor outcomes in very low birth weight infants. A multicenter cohort study. - Elena Chesi; Katia Rossi; Gina Ancora; Cecilia Baraldi; Mara Corradi; Francesco Di Dio; Giorgia Di Fazzio; Silvia Galletti; Giovanna Mescoli; Irene Papa; Agostina Solinas; Luca Braglia; et al. (PLoS ONE, 2024)
Objectives To standardize the diagnosis of patent ductus arteriosus (PDA) and report its association with adverse neonatal outcomes in very low birth weight infants (VLBW, birth weight < 1500 g). Study design A multicenter prospective observational study was conducted in Emilia Romagna from March 2018 to October 2019. The association between ultrasound grading of PDA and adverse neonatal outcomes was evaluated after correction for gestational age. A diagnosis of hemodynamically significant PDA (hsPDA) was established when the PDA diameter was ≥ 1.6 mm at the pulmonary end with growing or pulsatile flow pattern, and at least 2 of 3 indexes of pulmonary overcirculation and/or systemic hypoperfusion were present. Results 218 VLBW infants were included. Among infants treated for PDA closure in the first postnatal week, up to 40% did not have hsPDA on ultrasound, but experienced clinical worsening. The risk of death was 15 times higher among neonates with non-hemodynamically significant PDA (non-hsPDA) compared to neonates with no PDA. In contrast, the risk of death was similar between neonates with hsPDA and neonates with no PDA. The occurrence of BPD was 6-fold higher among neonates with hsPDA, with no apparent beneficial role of early treatment for PDA closure. The risk of IVH (grade ≥ 3) and ROP (grade ≥ 3) increased by 8.7-fold and 18-fold, respectively, when both systemic hypoperfusion and pulmonary overcirculation were present in hsPDA. Conclusions The increased risk of mortality in neonates with non-hsPDA underscores the potential inadequacy of criteria for defining hsPDA within the first 3 postnatal days (as they may be adversely affected by other clinically severe factors, i.e. persistent pulmonary hypertension and mechanical ventilation). Parameters such as length, diameter, and morphology may serve as more suitable ultrasound indicators during this period, to be combined with clinical data for individualized management. Additionally, BPD, IVH (grade ≥ 3) and ROP (grade ≥ 3) are associated with hsPDA. The existence of an optimal timeframe for closing PDA to minimize these adverse neonatal outcomes remains uncertain.